Líflínan – reynsla fólks með alvarlegan psoriasis sem er í meðferð með lífefnalyfjum - Inga Þorbjörg Steindórsdóttir; Þóra Jenný Gunnarsdóttir; Helga Jónsdóttir (Félag íslenskra hjúkrunarfræðinga, 2012)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Allur texti - Full text The prevalence of chronic diseases is increasing with consequent increased demands on the healthcare system for efficient treatments. One of these diseases is psoriasis for which, in Iceland, seriously ill patients have been treated with bio pharmaceuticals for the past decade. The goal of this study was to describe the experience of patients with serious psoriasis currently receiving infliximab (Remicade®). The research question was: What is the experience of patients with serious psoriasis undergoing treatment with Remicade®? The research method was hermeneutic phenomenology. A purposeful sample was selected with four women and three men aged 2745 years who were receiving regular treatment. Data were collected by interviewing each participant twice. The data were analysed according to van Manen’s method into the following fundamental lifeworld themes: Lived space: “Safety in isolation” and “Freedom that came with the treatment”. Lived time: “For a long time it was just the disease”, “Race against time” and “Worrying about the future”. Lived relation: “Shame and hiding”, “Troubles with making a connection” and “Communicating in the labyrinth”. Lived body: “The disease took all control” and “Incredible stress”. The essential theme was: “The treatment as a lifeline”. The severity of the disease over a number of years prior to infliximab treatment resulted in shame, incapacity and feelings of defeat and despair. Upon treatment however, participants reported drastic improvements in their quality of life but pinpointed that their initial concern over the long term effectiveness of infliximab was real. It is concluded that the participants would benefit from a continuous, familyoriented and comprehensive interdisciplinary healthcare service in order to increase the security and quality of life of these individuals. Langvinnum sjúkdómum fer fjölgandi hér á landi sem gera auknar kröfur til ...